SISTEM PENDUKUNG KEPUTUSAN PENENTUAN DOSEN TERBAIK PADA STMIK KRISTEN NEUMANN INDONESIA DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Elviani Br Tarigan; Ertina Sabarita Barus (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2018)
ecision support system aims to help managers or leaders to determine the best lecturers by considering several aspects as well as by giving importance to each aspect assessed. Based on this to determine the best lecturer, the method is used. The method used is Simple Additive Weighting (SAW). The study was conductedby finding the weight value of each criterion, and then normalizing the decision matrix to a scale that can be compared with all existing alternative ratings. The results of the calculation of this method are the results of ranking.